Learning a Foreign Language in Older Adults Shapes the Functional Connectivity of Distinct Cerebellar Sub‐Regions With Cortical Areas Rich in CB1 Receptor Expression - Giovanna Bubbico; Federica Tomaiuolo; Carlo Sestieri; Golnoush Akhlaghipour; Alberto Granzotto; Antonio Ferretti; Mauro Gianni Perrucci; Stefano L. Sensi; Stefano Delli Pizzi (Brain and Behavior)
ABSTRACT Background Foreign language learning (FLL) in older adults is a comprehensive cognitive enhancement tool that integrates linguistic, cognitive, and social components to stimulate neuroplasticity and promote brain reorganization to counteract age‐related decline. While previous studies have investigated the impact of FLL on the cortical connectome, its effects on subcortical‐cortical resting‐state functional connectivity (rs‐FC) remain unexplored. The present study focuses on the connectivity of the cerebellum, based on its involvement in learning and aging. We hypothesize that FLL primarily modulates the rs‐FC of the most “cognitive” cerebellar sub‐regions, such as the crus and the posterior lobules. Methods The rs‐FC pattern was analyzed in 27 participants who underwent a 4‐week FLL (n = 14) or a control (n = 13) protocol. Using distinct cerebellar regions as seeds in voxel‐wise analyses, we evaluated FLL‐induced changes in cerebellar–neocortical connectivity. Furthermore, we quantitatively assessed the spatial overlap between the connectivity modulations and the expression of neurotransmitter receptors associated with neuroplasticity, using data from publicly available repositories. Results The FLL group showed distinct changes in cerebellar‐neocortical rs‐FC, including reduced connectivity between Crus I/Vermis IV‐V and the visual cortex and increased connectivity between Lobule VI/VIIb and frontal regions. The connectivity changes involving Crus I and Lobule VI spatially overlapped with the distribution of CB1 receptors and, to a lesser extent, between the connectivity changes of Crus I/Lobule VI and Vermis IV‐V and mGluR5/GABAa receptors. Conclusions We provide new insights into the involvement of the cerebellum in the beneficial effects of FLL in aging, further highlighting the role of CB1 receptors and, secondarily, mGluR5/GABAa receptors.